2011
DOI: 10.1007/s12032-011-9900-5
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin-1 is related to invasion, survival, and poor prognosis in hepatocellular cancer

Abstract: Caveolin-1 is the principal components of caveolae membranes, implicated in oncogenesis and angiogenesis. Until now, its expression and functional significance in hepatocellular carcinoma (HCC) are still unclear. In the present study, we demonstrated that expression of caveolin-1 was markedly upregulated in HCC patients. In addition, increased caveolin-1 expression correlated positively with the histological differentiation, portal venous invasion, hepatic venous invasion, intrahepatic metastases, and recurren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 27 publications
0
45
0
Order By: Relevance
“…It has been reported that elevated expression of Cav-1 is associated with the development of resistance in hepatocellular cancer cells to paclitaxel (27). Additionally, Cav-1 participates in cell survival, tumor progression, metastasis and poor prognosis (19)(20)(21)(22). Cav-1 has been found to be correlated with colon cancer growth, metastasis and tumorigenicity (34,35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that elevated expression of Cav-1 is associated with the development of resistance in hepatocellular cancer cells to paclitaxel (27). Additionally, Cav-1 participates in cell survival, tumor progression, metastasis and poor prognosis (19)(20)(21)(22). Cav-1 has been found to be correlated with colon cancer growth, metastasis and tumorigenicity (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…Cav-1, as the principal component of caveolae, plays an important role in material transportation, endothelial infiltration and tumorigenesis (18). Cav-1 acts as a scaffolding protein by interacting with signaling molecules through a caveolin scaffolding domain to modulate gene expression, signal transduction and protein translocation in the cell membrane (18 invasion and metastasis (19)(20)(21)(22). Additionally, it has been shown that Cav-1 is closely associated with the development of drug resistance (23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…Caveolin-1 (Cav-1) has received the most attention, since its expression has been linked to cancer progression and aggressiveness (58). Cav-1 plays a role not only in cell death and survival, but also in cell migration (38) and invasion (61).…”
Section: Caveolin-1 Downregulation By Cnpmentioning
confidence: 99%
“…Similarly, Cav-1 protein was dysregulated in several other gastrointestinal cancers. Tumoral Cav-1 expression increased in cancers cells compared to their normal counterparts, whereas stromal Cav-1 expression decreased in cancer tissues compared to adjacent normal tissues, such as pancreatic cancer [9,19], esophageal cancer [20], and hepatocellular carcinomas [21]. Cav-1 expression is known to be regulated mainly by inactivation of oncogenes or inactivation of tumor suppressive genes, TGF-β, and oxidative stress in the tumor microenvironment [22,23].…”
Section: Discussionmentioning
confidence: 99%